Sorveglianza globale e metropoli pandemica. Attualità e genealogia di un disastro - Marzocca, Ottavio (Scienze del Territorio, 2020)
The SARS-COV2 pandemic has shown that entrusting global communications systems with public health protection can produce disastrous results. In fact, the strategies of planetary surveillance, promoted by the World Health Organization for the prevention of EIDs that have long been the greatest danger of pandemic infections, are oriented in this sense. These strategies are based, on the one hand, on the problematic willingness of nation-states to promptly communicate information on the risks of epidemics and, on the other hand, on the algorithmic processing of large masses of disparate data derived from web users behaviours. The growth of urban concentrations – the subject of anti-epidemic biopolitics since the beginnings of modernity and today recognized as a determining factor of the ecosystem alterations that cause pandemic dangers – in this scenario risks becoming a tendency to resign oneself to, waiting for the next contagion. The territorialist approach can offer alternative perspectives to this both by promoting and applying the idea of ​​ urban bioregion and by taking into account that there are already those who plan to transfer most of the ‘dangerous liaisons’ that take place in the postmodern metropolis online.